A diafiltration-nanofiltration-reverse osmosis (DiaNF-RO) process for brine management in seawater reverse osmosis (SWRO) desalination - Truong, Vinh Hien (2023)
In recent years, brine management in seawater reverse osmosis (SWRO) desalination has been more emphasized to reduce environmental hazards and recover valuable resources. However, current brine treatment methods are often hindered by the high brine concentration and energy consumption. To mitigate these challenges, this work applies a diafiltration-nanofiltration-reverse osmosis (DiaNF-RO) process, which aims to achieve divalent-monovalent ion separation in the pre-treatment step prior to RO. The diafiltration process is to enhance the separation performance of NF stage, while the RO stage is to produce the desalinated water and the diluent required by the diafiltration process. This study would justify the benefits of pre-treatment method (i.e., DiaNF-RO) over post-treatment method (i.e., RO-DiaNF), Fig. 1, in brine management by comparing the processes in 3 aspects (i.e., performance, operation, economic) via practical simulations, including pressure drop within module and concentration polarization (CP) effect, at the same number of stages and system water recovery, under similar input conditions such as NF/RO pressures and NF recovery rates.